Moodle 2.5 multimedia cookbook : 75 recipes to help you integrate different multimedia resources into your Moodle courses to make them more interactive /: 75 recipes to help you integrate different multimedia resources into your Moodle courses to make them more interactive. (2013) - Unknown
No abstract available